IVIG Treatment and Prognosis in Guillain–Barré Syndrome - van Doorn, Pieter A. (Springer US, 2010)
INTRODUCTION: Guillain–Barré syndrome (GBS) is an acute, immune-mediated polyneuropathy that often leads to severe weakness. Intravenous immunoglobulin (IVIG) is a proven effective treatment for GBS (class 1 evidence). However, about 25% of patients need artificial ventilation and 20% are still unable to walk unaided after 6 months. Important clinical factors associated with poor outcome are age, presence of preceding diarrhea and the severity of disability in the early course of disease. These clinical factors were combined in a clinical prognostic scoring scale, the Erasmus GBS Outcome Scale (EGOS). MATERIALS AND METHODS: GBS patients being unable to walk unaided are currently treated with a standard single IVIg dose (0.4 g/kg bodyweight for 5 days). A recent retrospective study in 174 GBS patients enrolled in one of our randomized controlled clinical trials showed that patients with a minor increase of serum IgG level after standard single IVIg dose recovered significantly slower. Additionally, fewer patients reached the ability to walk unaided at six months after correction for the known clinical prognostic factors (multivariate analysis; P < 0.022). DISCUSSION: It is yet unknown why some GBS patients only have a minor increase after standard IVIg treatment. By using the EGOS it is possible to select GBS patients with a poor prognosis. These patients potentially may benefit from a second IVIg dose. CONCLUSION: A standard dose of IVIG is not sufficiently effective in many GBS patients. Whether these patients might benefit from a second IVIg dose needs further investigation.